2021
DOI: 10.1142/s0217732321501224
|View full text |Cite
|
Sign up to set email alerts
|

Deriving the dark matter-dark energy interaction term in the continuity equation from the Boltzmann equation

Abstract: Dark energy and dark matter are two of the biggest mysteries of modern cosmology, and our understanding of their fundamental nature is incomplete. Many parametrizations of couplings between the two in the continuity equation have been studied in the literature, and observational data from the growth of perturbations can constrain these parametrizations. Assuming standard general relativity with a simple Yukawa-type coupling between dark energy and dark matter fields in the Lagrangian, we use the Boltzmann equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Some theoretical effort has gone into providing a theoretical footing to the interaction kernels, well using a scalar field description [84,269] or deriving them from the continuity and Boltzmann equations [231,232]. In [191] it was demonstrated that a classical field and a fluid description are consistent only for a very specific interaction kernel.…”
Section: Recent Progress In Ide Modelsmentioning
confidence: 99%
“…Some theoretical effort has gone into providing a theoretical footing to the interaction kernels, well using a scalar field description [84,269] or deriving them from the continuity and Boltzmann equations [231,232]. In [191] it was demonstrated that a classical field and a fluid description are consistent only for a very specific interaction kernel.…”
Section: Recent Progress In Ide Modelsmentioning
confidence: 99%